2021
DOI: 10.4038/cbj.v12i1.76
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Economic Efficiency of Small-Scale Rubber Plantations: With Special Reference to Kalutara District in Sri Lanka

Abstract: The Rubber Industry has been a major partner in the Sri Lankan economy. According to the literature, farmers in developing countries have failed to achieve full potential of Technical Efficiency (TE) and Allocative Efficiency (AE). This paper investigates the Economic Efficiency (EE) of Small Rubber Plantation Owners (SRPOs) in Sri Lanka by employing stochastic production frontier using a sample of 120 SRPOs. The results showed that the average TE of selected SRPOs is 82.86%. This indicates that output can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Rubber farming experience has a significant and positive effect on TE and EE; this implies that rubber farming experience can improve technical and economic efficiency in smallholder rubber plantations. This finding differs from the research by Giroh and Adebayo [30] and Harshani and Shantha [43], which concluded that experience in rubber farming does not affect the inefficiency of smallholder rubber plantations. However, this research is supported by the findings of Aliyu et al [36] and Syarifa [27], which stated that the rubber farming experience plays an important role in reducing the inefficiency of rubber plantations.…”
Section: Determinants Of the Efficiency Of Smallholder Rubber Plantat...contrasting
confidence: 99%
See 1 more Smart Citation
“…Rubber farming experience has a significant and positive effect on TE and EE; this implies that rubber farming experience can improve technical and economic efficiency in smallholder rubber plantations. This finding differs from the research by Giroh and Adebayo [30] and Harshani and Shantha [43], which concluded that experience in rubber farming does not affect the inefficiency of smallholder rubber plantations. However, this research is supported by the findings of Aliyu et al [36] and Syarifa [27], which stated that the rubber farming experience plays an important role in reducing the inefficiency of rubber plantations.…”
Section: Determinants Of the Efficiency Of Smallholder Rubber Plantat...contrasting
confidence: 99%
“…This differs from the research results by Aliyu et al [36], which stated that gender does not affect the inefficiency of smallholder rubber plantations. Giroh and Adebayo [30,32], Harshani and Shantha [43], and Poungchompu and Chantanop [31] argued differently; they concluded that gender plays an important role in increasing the efficiency of smallholder rubber plantations. The same thing was stated by Gbigbi [41] that women managers also play a role in the agricultural sector.…”
Section: Determinants Of the Efficiency Of Smallholder Rubber Plantat...mentioning
confidence: 99%
“…The model for cross-sectional data is Y = f (Xiα) e εi (i = …..n) as defined by Aigner et al,[15], Meeusen and Broeck [16], Battese and Coelli [17] where, Yi = Output of the i th farmer, Xi = input quantities used of i th farmer, α = parameters to be estimated, εi = A stochastic error-term consisting of two independent components Ui and Vi, and εi = Vi -Ui. [18,19].…”
Section: Stochastic Frontier Production Functionmentioning
confidence: 99%
“…Gunarathna et al (2023) observed the present socioeconomic issues and conditions faced by smallholder rubber farmers in the Monaragala district. Harshani et al (2021) examined the economic efficiency and its associated concerns of small rubber plantations in the Kaluthara district. Although there exist certain observations regarding the current issues of the rubber industry in different parts of the country, no research has been conducted in the Pahala Karannagoda area (GN Division: No-811A, Code-100), which is situated in the Madurawela Divisional Secretariat Area of the Kalutara District in the Western province.…”
Section: Justifications For the Selection Of Research Areamentioning
confidence: 99%